Життя і діяльність професора О.І. Соколовського - Peregrym, M.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2005)
The life and scientific activity of the outstanding scientist and the teacher, the first chief of department of flora and vegetation of U.S.S.R. of Central Republican Botanical Gardens of Professor O.I. Sokolovsky are described.